2015
DOI: 10.4238/2015.december.21.37
|View full text |Cite
|
Sign up to set email alerts
|

Association of regulator of G protein signaling (RGS5) gene variants and essential hypertension in Mongolian and Han populations

Abstract: ABSTRACT. Genetic variants of the RGS5 gene are believed to be risk factors for hypertension and cardiovascular diseases. In this study, we investigated the association between RGS5 gene variants and hypertension in the Mongolian and Han populations. Peripheral blood was obtained from 429 unrelated Mongolian herdsmen and 416 Han farmers [including essential hypertension (EH) patients and controls]. Nine tagSNPs within the RGS5 genes were retrieved from HapMap, and the samples were individually genotyped using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…RGS5 is a family member that is highly expressed in vSMCs and plays a pivotal role in vascular pathologies (Box 3). RGS5 is a negative modulator of AngII/ATR1 signaling in vitro and in humans RGS5 gene polymorphism has been associated with hypertension in the general population [60][61][62] 22 (Table 1) protecting from atherosclerotic plaque formation has been demonstrated in RGS5 gene deficient mice [73]. Similar to PPARs, RGS5 appears to protect from sequelae of the metabolic syndrome such as diet-induced obesity, hepatic steatosis, inflammation, and insulin resistance [76].…”
Section: Rgs5 and Pregnancy-associated Hypertensionmentioning
confidence: 99%
“…RGS5 is a family member that is highly expressed in vSMCs and plays a pivotal role in vascular pathologies (Box 3). RGS5 is a negative modulator of AngII/ATR1 signaling in vitro and in humans RGS5 gene polymorphism has been associated with hypertension in the general population [60][61][62] 22 (Table 1) protecting from atherosclerotic plaque formation has been demonstrated in RGS5 gene deficient mice [73]. Similar to PPARs, RGS5 appears to protect from sequelae of the metabolic syndrome such as diet-induced obesity, hepatic steatosis, inflammation, and insulin resistance [76].…”
Section: Rgs5 and Pregnancy-associated Hypertensionmentioning
confidence: 99%
“…A study demonstrated that RGS5 may be a candidate target gene for the treatment of human and animal www.nature.com/scientificreports www.nature.com/scientificreports/ hypertension. Indeed, RGS5 genetic polymorphisms have been shown to be associated with human hypertension 39 . Additionally, the expression level of RGS5 in the vascular smooth muscle and intima was markedly reduced in spontaneously hypertensive rats and adrenocorticotropic hormone-and Ang-II-induced hypertensive rats, while the blood pressure level was increased in RGS5-knockout mice 37,40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 40 ligase detection reaction cycles were performed under conditions of 92°C for 2 min, 94°C for 15 s, and 50°C for 25 s. The fluorescent products of ligase detection reaction were identified by PRISM 3730 (ABI). The experimental methods are similar to Chang et al [15].…”
Section: Methodsmentioning
confidence: 99%